Tailored Mobility in a Zeolite Imidazolate Framework (ZIF) Antibody Conjugate. Issue 36 (21st May 2021) - Chapartegui‐Arias, Ander; Raysyan, Anna; Belenguer, Ana M.; Jaeger, Carsten; Tchipilov, Teodor; Prinz, Carsten; Abad, Carlos; Beyer, Sebastian; Schneider, Rudolf J.; Emmerling, Franziska
Abstract: Zeolitic imidazolate framework (ZIF) hybrid fluorescent nanoparticles and ZIF antibody conjugates have been synthesized, characterized, and employed in lateral‐flow immunoassay (LFIA). The bright fluorescence of the conjugates and the possibility to tailor their mobility gives a huge potential for diagnostic assays. An enzyme‐linked immunosorbent assay (ELISA) with horseradish peroxidase (HRP) as label, proved the integrity, stability, and dispersibility of the antibody conjugates, LC‐MS/MS provided evidence that a covalent link was established between these metal‐organic frameworks and lysine residues in IgG antibodies. Abstract : Framing an assay : We present nanosized zeolitic imidazolate frameworks (ZIFs) conjugated to immunoglobulin G (IgG) antibodies by using a strong and flexible covalent amino‐alkyl link. These nanoZIF‐IgG particles display good mobility and an excellent behaviour in dispersion. Their application to antibody‐based bioanalytical assays, including enzyme‐linked immunosorbent assay (ELISA) and lateral flow immunoassay (LFIA), was examined.